Development of Sharaf Learning Materials Based on a Communicative Approach to Enhance Students’ Language Proficiency in an Islamic University - Sam, Zulfiah; Kasim, Amrah; Haniah, Haniah; Hamzah, A. Abdul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to develop learning materials for Sharaf based on a communicative approach to address the limitations of existing instructional practices that have not optimally enhanced students’ Arabic speaking skills (mahārah al-kalām). It also seeks to examine the validity, practicality, and effectiveness of the developed materials among students at STIBA Islamic Institute of Makassar. The research employed a design and development research approach consisting of several stages: needs analysis, design, development, and evaluation. The research data consisted of both quantitative and qualitative data obtained from 30 first-semester students as well as subject-matter experts and instructional design experts. Data were collected through expert validation sheets, student response questionnaires, observation sheets, and pretest–posttest assessments of Arabic language proficiency. The data were then analyzed using descriptive quantitative and qualitative analysis to determine the validity, practicality, and effectiveness of the developed learning materials. The findings reveal that the developed materials demonstrate a very high level of validity, with an average score of 3.97, and are considered practical and engaging based on positive student responses and observations of the learning implementation. The effectiveness test indicates a significant improvement in students’ speaking ability after the use of the learning materials, with an N-gain score of 0.41, which falls into the moderate category. These findings suggest that integrating Sharaf rules into meaningful communicative activities can bridge the gap between students’ mastery of linguistic structures and their ability to apply them in Arabic-speaking practice. Therefore, Sharaf learning materials based on a communicative approach are suitable to be used as an innovative alternative in teaching Sharaf at Islamic higher education institutions.